Examining the correlation between symptoms of obsessive compulsive disorder and autism spectrum disorder in a community-based sample of adults. (May 2021) - Barnard-Brak, Lucy; Watkins, Laci; Richman, David M.
Highlights: We examined the association between obsessive compulsive disorder (OCD) and autism spectrum disorder (ASD) symptoms among a community-based sample of adults. The correlation between overall OCD symptoms (i.e., obsessions and compulsions) and ASD symptoms was small but statistically significant. Similarly, obsession and compulsion subscales showed almost identical results for correlation with ASD symptoms (i.e., small but statistically significant) for the entire sample. Abstract: We examined the association between obsessive compulsive disorder (OCD) and autism spectrum disorder (ASD) symptoms among a community-based sample of adults ( n = 217) that completed an OCD and ASD screening instrument. Approximately 39% of the sample that met the ASD screener cutoff criteria also met the screener cutoff criteria for OCD. The correlation between overall OCD symptoms (i.e., obsessions and compulsions) and ASD symptoms was small but statistically significant for the entire sample of participants. Similarly, obsession and compulsion subscales showed almost identical results for correlation with ASD symptoms (i.e., small but statistically significant) for the entire sample. These results suggest that levels of compulsions and obsessions are equally correlated with ASD symptoms, and neither elevated compulsions nor obsessions differentially predicted the severity of ASD symptoms in a community-based sample of adults. However, when the analysis was restricted to only the participants that met screening criteria cutoff score for ASD, statistically significant results occurred with only elevated compulsions accurately predicting severity of ASD symptoms. These results suggest that compulsive behavior appears to be a good candidate for targeting intervention resources for individuals with characteristics of ASD given the mounting data suggesting that compulsions are more common than obsessions.